Boron Clusters as a Platform for New Materials: Synthesis of Functionalized o‐Carborane (C2B10H12) Derivatives Incorporating DNA Fragments. Issue 43 (8th September 2015) - Janczak, Slawomir; Olejniczak, Agnieszka; Balabańska, Sandra; Chmielewski, Marcin K.; Lupu, Marius; Viñas, Clara; Lesnikowski, Zbigniew J.
Abstract A synthetic strategy for functionalization of the three vertices of o‐carborane and the attachment of the obtained triped to the solid support was developed. Further functionalization of the triped with short DNA sequences by automated DNA synthesis was achieved. The proposed methodology is a first example of boron cluster chemistry on a solid support opening new perspectives in boron cluster functionalization.